Role of AE2 for pHi regulation in biliary epithelial cells - Concepcion, Axel R.; Lopez, María; Ardura-Fabregat, Alberto; Medina, Juan F. (Frontiers in Physiology, 2014)
The Cl-/HCO3- anion exchanger 2 (AE2) is known to be involved in intracellular pH (pHi) regulation and transepithelial acid-base transport. Early studies showed that AE2 gene expression is reduced in liver biopsies and blood mononuclear cells from patients with primary biliary cirrhosis (PBC), a disease characterized by chronic nonsuppurative cholangitis associated with antimitochondrial antibodies (AMA) and other autoimmune phenomena. Microfluorimetric analysis of the Cl-/HCO3- anion exchange (AE) in isolated cholangiocytes showed that the cAMP-stimulated AE activity is diminished in PBC compared to both healthy and diseased controls. More recently, it was found that miR-506 is upregulated in cholangiocytes of PBC patients and that AE2 may be a target of miR-506. Additional evidence for a pathogenic role of AE2 dysregulation in PBC was obtained with Ae2a,b-/- mice, which develop biochemical, histological, and immunologic alterations that resemble PBC (including development of serum AMA). Analysis of HCO3- transport systems and pHi regulation in cholangiocytes from normal and Ae2a,b-/- mice confirmed that AE2 is the transporter responsible for the Cl–/HCO3– exchange in these cells. On the other hand, both Ae2a,b+/+ and Ae2a,b-/- mouse cholangiocytes exhibited a Cl–independent bicarbonate transport system, essentially a Na+-bicarbonate cotransport (NBC) system, which could contribute to pHi regulation in the absence of AE2.